2015
DOI: 10.3109/02699052.2015.1005131
|View full text |Cite
|
Sign up to set email alerts
|

The role of apolipoprotein E episilon (ɛ)-4 allele on outcome following traumatic brain injury: A systematic review

Abstract: The influence of APOEε4 on neuropsychological testing, functional outcome and in paediatric populations was incongruous. This review supports the majority of research indicating APOEε4 adversely influences recovery following TBI, particularly with respect to dementia-related outcomes and outcomes following sTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 118 publications
6
49
3
Order By: Relevance
“…27 Experimental data indicate that TBI in triple transgenic AD model mice causes accumulation and aggregation of Ab oligomers in the brain, which may contribute to developing AD later in life. 40 Genetic factors, such as presence of an ApoE4 allele 44 or neprilysin gene transfer (GT) repeat polymorphism 45 may potentially explain the bimodal distribution of Ab42 after TBI. Testing such a hypothesis will require a larger sample size, as the number of patients in our cohort was too small to allow adequately powered allelic association studies.…”
Section: Discussionmentioning
confidence: 99%
“…27 Experimental data indicate that TBI in triple transgenic AD model mice causes accumulation and aggregation of Ab oligomers in the brain, which may contribute to developing AD later in life. 40 Genetic factors, such as presence of an ApoE4 allele 44 or neprilysin gene transfer (GT) repeat polymorphism 45 may potentially explain the bimodal distribution of Ab42 after TBI. Testing such a hypothesis will require a larger sample size, as the number of patients in our cohort was too small to allow adequately powered allelic association studies.…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that moderate-to-severe TBI was associated with a higher likelihood for developing dementia in persons aged 55 years and older, whereas a single, mild TBI was associated with increased risk among those older than 64 years. In addition, a “synergistic” link between Apoe4 and a history of TBI is even less clear, as this literature too has been mixed, with approximately 50% of studies reporting an absence of an additive effect on increasing risk for developing dementia (Lawrence, Comper, Hutchison, & Sharma, 2015). More severe TBI may be an important factor (Lawrence et al, 2015), but some Apoe4 carriers could also possess the Apoe ε2 (Apoe2) allele (genotype ε2/ ε4), which has been implicated as protective against neuronal injury (Miller et al, 2010) and from AD (Corder et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a “synergistic” link between Apoe4 and a history of TBI is even less clear, as this literature too has been mixed, with approximately 50% of studies reporting an absence of an additive effect on increasing risk for developing dementia (Lawrence, Comper, Hutchison, & Sharma, 2015). More severe TBI may be an important factor (Lawrence et al, 2015), but some Apoe4 carriers could also possess the Apoe ε2 (Apoe2) allele (genotype ε2/ ε4), which has been implicated as protective against neuronal injury (Miller et al, 2010) and from AD (Corder et al, 1994). It is possible that the presence of Apoe2 may offset Apoe4’s role in initiating and/or accelerating AD-like pathology, protecting against synergist mechanisms following TBI in some individuals, which could attenuate differences when comparing Apoe4 carriers to non-carriers.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE ε3 has a neuroprotective effect that protects against neurodegeneration and cognitive decline, while ApoE ε4 has the opposite effect, resulting in an overall negative influence on several neuroplastic processes. 66, 67 The ApoE ε4 allele is a risk factor for Alzheimer’s disease 68 and is related to poorer outcome after traumatic brain injury 69 and stroke. 7072 …”
Section: Genetic Polymorphisms Neuroplasticity and Motor Learningmentioning
confidence: 99%